Parents' willingness to pay for their children's COVID-19 vaccine in Taiwan, China: A cross-sectional study. Issue 1 (31st December 2023) - Huang, Chun-Lian; Chen, Jau-Yuan; Lin, Xiao-Qing; Deng, Jing-Shan; Tung, Tao-Hsin; Zhu, Jian-Sheng
ABSTRACT: Most COVID-19 studies aim to assess factors influencing willingness to pay for vaccines between the public and medical staff. However, few studies focus on parents' willingness to pay for their children's COVID-19 vaccine. The current study aimed to assess parents' willingness to pay for their children's vaccination against COVID-19 and its influencing factors. This population-based cross-sectional study used a self-administered questionnaire. The inclusion criterion was parents with at least one child younger than 18 years. The final analysis included 384 valid data points. A total of 89.1% of the parents indicated that they are willing to pay for their children's vaccination against COVID-19. Among them, both fathers' and mothers' willingness to pay for their children's COVID-19 vaccine was 89.6%. The mean and median willingness to pay were% would pay for their children. Excluding other confounding factors, willingness to pay for the COVID-19 vaccine for themselves and hesitation to vaccinate their children were significantly associated with parents' willingness to pay for their children's COVID-19 vaccine. We found that 89.1% of the parents in Taiwan would pay for their children's COVID-19 vaccine. Parents' willingness to pay for themselves and hesitation to vaccinate their children were associated with willingness to pay. Reducing hesitation about vaccines and developing policies for vaccine payment may have a positive impact on willingness to pay for vaccines and promoting COVID-19 vaccination.